Restrukturisasi Kognitif untuk Meningkatkan Harga Diri pada Remaja dengan Perilaku Menghindar Pascaperundungan: Sebuah Studi Kasus di Lingkungan Sekolah Kejuruan - Ranti Sagita; Niken Titi Pratitis (LPPM STAI Muhammadiyah Probolinggo, 2026)
Persistent mask use after bullying may reflect low self-esteem and function as a safety behavior that reduces anxiety temporarily while maintaining fear of negative evaluation. This study describes the psychological dynamics of a 17-year-old vocational high school student (AR) and examines early changes following individual counseling based on cognitive restructuring. A descriptive-exploratory single-case design was used. Data were collected through semi-structured interviews with the participant and supporting informants, non-participant observations at the internship site, document review, and psychological assessment using the 16PF, SSCT, Draw A Person, House-Tree-Person, and Rosenberg Self-Esteem Scale. Thematic analysis and source-method triangulation were guided by Beck's cognitive model, Ellis' ABC framework, and Rosenberg's self-esteem theory. Repeated verbal bullying about physical appearance consolidated a negative self-schema, while mask use developed into a safety behavior maintained by negative reinforcement. Six counseling sessions addressed psychoeducation, emotion identification, ABC analysis, cognitive disputation, adaptive coping thoughts, graded behavior change, and relapse-prevention planning. Post-intervention data indicated greater emotional openness, willingness to eat and drink at school, voluntary mask removal in selected situations, and more balanced self-statements. The findings represent clinically meaningful early change, not causal proof, because numerical pre-post data and long-term follow-up were unavailable.